Absence of superconductivity and density-wave transition in ambient-pressure tetragonal La4Ni3O10 - Mengzhu Shi; Yikang Li; Yuxing Wang; Di Peng; Shaohua Yang; Houpu Li; Kaibao Fan; Kun Jiang; Junfeng He; Qiaoshi Zeng; Dongsheng Song; Binghui Ge; et al. (Nature Communications)
Abstract The recent discovery of superconductivity in La3Ni2O7 and La4Ni3O10 under pressure stimulates intensive research interests. These nickelates crystallize in an orthogonal/monoclinic structure and have a density-wave transition at ambient pressure. The application of pressure triggers a transition to tetragonal structure (I4/mmm), which is believed to be a key prerequisite for the emergence of superconductivity. Here, we report the first tetragonal nickelates La4Ni3O10 microcrystals at ambient pressure. In tetragonal La4Ni3O10, transport measurements find that both density-wave and superconducting transitions are absent up to 160 GPa, indicating a robust tetragonal metallic ground state. Meanwhile, density functional theory calculations reveal a considerable contribution of d z2 orbital to the Fermi surface. The concurrent absence of density-wave state and high-pressure superconductivity in tetragonal La4Ni3O10 suggests that the density-wave state instead of tetragonal structure is crucial for the superconductivity in nickelates under pressure. Our findings impose important constraints on the mechanism of pressure-induced superconductivity in nickelates.